Deskripsi Level Pengetahuan Konten Matematika Mahasiswa Calon Guru dalam Menyelesaikan Masalah Definisi Grup - Sa’adah, Nihayatus; Ramadhani, Rahma (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
The knowledge possessed by teachers is closely related to the achievements achieved by students. Therefore, how rich the knowledge possessed by a teacher is important to know. This study aimed to describe the level of mathematical content knowledge preservice teacher students in solving group definition problems. The subjects were two different gender students with equivalent academic ability. The data were collected with the researchers as the main instrument and the test as the supporter one. The test was arranged to reveal how the subjects stated the definition, used mathematical notation and saw the connection between the different topics. The data was analyzed by reducing data, presenting data, and drawing the conclusion. The result of this study shows that: (1) the female subject was able to express the definitions correctly, use appropriate notation sensibly, and see connections between different topics and move among them smoothly so it can be concluded that the female subject is on level 2 and (2) the male one was able to express the definitions correctly but unable to use appropriate notation sensibly, see connection between different topics but unable to move among them smoothly so it can be concluded that the male subject is on level 1.